Förster resonance energy transfer in poly(methyl methacrylates) copolymers bearing donor–acceptor 1, 3‐thiazole dyes. Issue 22 (9th September 2013) - Pietsch, Christian; Schäfer, Johann; Menzel, Roberto; Beckert, Rainer; Popp, Jürgen; Dietzek, Benjamin; Schubert, Ulrich S.
ABSTRACT The Förster resonance energy transfer (FRET) properties in poly(methyl methacrylate) copolymers containing 2‐(pyridine‐2‐yl) thiazole dyes were studied upon systematic variation of the donor‐to‐acceptor ratio. To this end, 2‐(pyridine‐2‐yl) thiazole dyes specially designed for the usage as energy donor and acceptor molecules were incorporated within one polymer chain. Poly(methyl methacrylate) copolymers containing these donor and acceptor dyes were synthesized using the RAFT polymerization method. Copolymers with a molar mass (Mn) of nearly 10, 000 g/mol were achieved with dispersity index values (Đ) under 1.3. The presented copolymers act as a model system for the FRET investigation. Förster resonance energy transfer properties of the copolymers are characterized by steady state as well as time resolved fluorescence spectroscopy. The results indicate that the energy transfer rates and the transfer efficiencies are tunable by variation of the donor‐acceptor‐ratio. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 4765–4773